Characteristics of shear-induced asperity degradation of rock fractures and implications for solute retardation. (May 2018) - Zhao, Zhihong; Peng, Huan; Wu, Wei; Chen, Yi-Feng
Abstract: Direct shear tests on a series of fractured Beishan granite samples were performed under different normal stresses, to investigate the characteristics of asperity degradation during shear and to quantify their effects on solute retardation in fractures. A three-dimensional laser scanner and a laser diffraction particle size analyzer were used to examine the shear-induced asperity volume loss and the size distribution of sheared-off fragments. The results identified two main modes of asperity degradation during shear, i.e., instantaneous failure of asperities occurring at the peak shear stress, and crushing of the generated fragments with further shear displacement. Based on the volume of asperity degradation, a new joint damage coefficient was proposed. The size of the sheared-off fragments under different normal stresses was found to follow a Weibull distribution. Combining the proposed joint damage coefficient and the Weibull size distribution of the sheared-off fragments can approximately predict the potential effects of sheared-off fragments on solute retardation coefficient in rock fractures. The results showed that the shear-induced asperity degradation significantly increases the values of the solute retardation coefficient, by offering more sorption surfaces in fracture voids.